Pengaruh Kreasi Nilai: Function/Instrumental Value, Experiental/ Hedonic Value, Symbolic/ Expressive Value dan Cost/Sacrefice Value terhadap Loyalitas Pelanggan - Rita Kusumadewi (IAIN Syekh Nurjati Cirebon, 2015)
AbstrakPerusahaan berusaha untuk membentuk kesetiaan pelanggan lama, dan sekaligus menarik pelanggan baru melalui kreasi nilai terhadap produk yang ditawarkannya. Loyalitas pelanggan tidak hanya menjadi kunci sukses jangka pendek tapi juga kunci sustainable competitive advantage, karena pada dasarnya melalui terpeliharanya loyalitas maka perusahaan akan profitable. Artikel ini akan mengkaji dan mengembangkan teori lama mengenai kreasi nilai melalui variabel functional/instrumental value, experiental/hedonic value, symbolic/ expressive value dan cost/sacrifice value terhadap customer loyalty. Dengan metode explanatory survey dan metode pengembangannya cross sectional maka dapat diperoleh hasil bahwa functional/instrumental value (FIV) dan experiental/ hedonic value (EHV) memiliki pengaruh yang lebih besar terhadap customer loyalty dibandingkan dengan symbolic/expressive value (SEV) dan cost/sacrifice value (CSV). Penurunan kesetiaan pelangan akan terjadi bila indikator-indikator ini tidak ditingkatkan atau tidak diperhatikan. Kata kunci: functional/instrumental value, experiental/ hedonic value, symbolic/ expressive value, cost/sacrifice value, loyalitas pelanggan AbstractThe company tried to establish customer loyalty, as well as attracting new customers through the creation of value of the product offerings. Customer loyalty is not only a short term key of success but also key to sustainable competitive advantage, because basically through the maintenance of loyalty the company will be more profitable. The purpose of this article are to assess and develop the old theory about the influence of value creation through functional/instrumental value, experimental/hedonic value, symbolic/expressive value and cost/sacrifice value to customer loyalty. By using explanatory survey method with cross sectional method as the result showed that the functional/instrumental value (FIV) and experiental/hedonic value (EHV) has bigger effect on customer loyalty than a symbolic/expressive value (SEV) and cost/sacrifice value (CSV). The decrease of customers loyalty will happen if these indicators were not being improve or watch. Keywords: customers value, functional/instrumental value, experiental/hedonic value, symboli/expressive value, cost/sacrifice value, customers loyalty